Second-Round Effects of Oil Price Shocks - Implications for Europe's Inflation Outlook - Baba, Chikako (IMF Working Papers; Working Paper ;, 2022)
The pass-through effects of oil price shocks on wage and consumer price inflation vary with the states or structural characteristics of an economy. The effects have declined over time in Europe and been higher in emerging European economies than in advanced economies. The pass-through to wages is found to have been higher when the prevailing level of inflation was higher or when the degrees of unionization and centralized bargaining were higher, while lower under a higher credibility of monetary policy. The effects of oil price shocks on core inflation and inflation expectations are consistent with their effects on wages.